Can price limit effectively reduce stock price volatility? An empirical evidence from Vietnam Stock Exchange - Nguyen, Thi Thuy Linh (2013)
The financial market crashes happen in 1987 has led to discussions regarding the effectiveness of different methods of market discipline. One of the mechanisms was suggested to be implemented is circuit breakers, including price limit.Daily price limits represent explicit boundaries that pre-specify the maximum range, usually both upward and downward, in which stock prices are allowed to move within a single day. Price limit is set in various stock market around the world since the regulators argue that it help reduce and control for stock price volatility by providing a cool-off period, especially during time of panic overreaction. However, opponents of price limit argue that there are several costs associated with it, namely volatility spill-over hypothesis, delay price discovery process hypothesis, trading interfere and magnet effect hypothesis. Being an important part of the microstructure of market, the effects of price limit in financial markets have already been explored by many researchers. However, the results are somewhat mixed. This study aims to provide new evidence to the current debate by examining the impact of price limit on volatility in a small emerging market, the Vietnam stock market. The paper finds that price limit effectively reduce the excessive volatility in Vietnam stock exchange.